2015
DOI: 10.5935/0004-2749.20150091
|View full text |Cite
|
Sign up to set email alerts
|

Optic coherence tomography measurement of choroidal and retinal thicknesses after uncomplicated YAG laser capsulotomy

Abstract: Approved by the following research ethics committee: Erciyes University Ethics Committee 2014/356. ABSTRACTPurpose: Optic coherence tomography (OCT) evaluation of the choroid, retina, and retinal nerve fiber layer after uncomplicated yttrium-aluminum-garnet (YAG) laser capsulotomy. Methods: OCT analysis of retinal and choroidal structures was performed in 28 eyes of 28 patients following routine examinations before and 24 h, 72 h, 2 weeks, 4 weeks, and 12 weeks after YAG laser capsulotomy. Data were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
3
2
0
1
Order By: Relevance
“…Those two studies and the previous studies examining the relationship between cataract surgery and choroid structure have suggested that postoperative inflammation may be responsible for increased choroidal thickness. [8][9][10][11] These results support the fact that inflammatory processes may assume an essential role in the change in choroidal thickness after Nd: YAG laser. As subfoveal and nasal areas are closer to the optical disc compared to the temporal region, the choroidal thickness change there requires more detailed studies concerning mechanisms.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Those two studies and the previous studies examining the relationship between cataract surgery and choroid structure have suggested that postoperative inflammation may be responsible for increased choroidal thickness. [8][9][10][11] These results support the fact that inflammatory processes may assume an essential role in the change in choroidal thickness after Nd: YAG laser. As subfoveal and nasal areas are closer to the optical disc compared to the temporal region, the choroidal thickness change there requires more detailed studies concerning mechanisms.…”
Section: Discussionsupporting
confidence: 71%
“…There were temporary or nonsignificant changes in the choroidal thicknesses after laser procedure in the aforementioned studies. 8,9 While temporary increases have been seen in the subfoveal and temporal areas also in our study; a significant increase has been observed only in the nasal choroidal thickness. The reason for this situation might be the lower energy content of the laser procedure performed in the previous study or the fluctuation of intraocular pressure induced by higher energy in our study.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Несколько групп авторов [38,39,[41][42][43] с помощью ОКТ исследовали состояние различных слоев сетчатки, хориоидеи, толщину сетчатки в макулятной области. Результаты этих исследований хорошо согласовались друг с другом и показывали тенденцию к утолщению сетчатки и хориоидеи, а также истончение слоя ретинальных нервных волокон.…”
Section: иаг-лазерная дисцизия вторичной катарактыunclassified